Social status and cultural consumption - Chan, Tak Wing. (Cambridge, UK : Cambridge University Press, 2010)
Leading scholars from around the world examine the social stratification of arts and culture in contemporary society.
Includes bibliographical references and index.
Keywords: Consumption (Economics) -- Social aspects; Social status